2018
DOI: 10.1177/1024258918775535
|View full text |Cite
|
Sign up to set email alerts
|

Labour, self-entrepreneurship in Brazil and paradoxes of social freedom

Abstract: In this article we shall explore, in the context of flexible capitalism, emerging forms of social insertion generated by work outside the realms of wage labour, in particular, so-called ‘self-entrepreneurship’ ( autoempreendedorismo). We shall argue that this phenomenon is related to the increase in contract-based employment, which amounts to a new employment regime. Self-management ( autogestão de si) is both a promising pathway to social insertion through work, and a way of internalising certain values. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 7 publications
0
6
0
1
Order By: Relevance
“…Here as well, through these three case studies it is interesting to observe the variations within that single sub-type of self-employment. They remind us of re-fragmentations, for example between "genuine self-entrepreneurs and subordinates" and "formal and informal sectors") observed in other gray zones, such as auto-entrepreneurship in Brazil (Rosenfield, 2018). They also advocate for alternatives to analytical oppositions between "entrepreneurship" and "precariousness" in the gray zones of work (Murgia and Azaïs, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Here as well, through these three case studies it is interesting to observe the variations within that single sub-type of self-employment. They remind us of re-fragmentations, for example between "genuine self-entrepreneurs and subordinates" and "formal and informal sectors") observed in other gray zones, such as auto-entrepreneurship in Brazil (Rosenfield, 2018). They also advocate for alternatives to analytical oppositions between "entrepreneurship" and "precariousness" in the gray zones of work (Murgia and Azaïs, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Understanding the dynamics of ableism and entrepreneurialism through the case of EWD advances knowledge on the paradoxes of social freedom (Rosenfield, 2018) in contemporary capitalist societies. Results have shown that by freeing oneself from the ableist discourse, EWD also distance themselves from the disability community and a “disabled social identity”.…”
Section: Discussionmentioning
confidence: 99%
“…Becoming an entrepreneur as a PWD is a complex social phenomena in terms freedom, as it can provide an opportunity to combat ableist, low-productivity discourse (Jammaers and Zanoni, 2020), providing the freedom of self-governance and self-organisation (Shir and Ryff, 2021) for PWD, however, construing the neoliberal subject of the entrepreneur might also limit reflexivity (Foster, 2017) or solidarity (Rosenfield, 2018). Using the critical theory of freedom, this study explores how becoming and being an entrepreneur reflects in the lived experience of freedom among PWD.…”
Section: Disability and Freedommentioning
confidence: 99%
“…-a first meaning of the term 'grey zone' designates more specifically the area of (inter)actions entirely or partially placed under the control or power of regulation of non-instituted actors (Bureau and Corsani, 2018;Dieuaide, 2018). We have reserved the term 'zone' to designate these situations, in line with the spirit of the various approaches developed by geopolitical experts (see introduction); -a second meaning refers to the margins of manoeuvre that exist within legal regulations, which both instituted and non-instituted actors seize upon to assert their rights or improve their working and employment conditions (Giraud and Lechevalier, 2018;Rosenfield, 2018). In Table 1, we chose to use the term 'space' to describe this kind of configuration.…”
Section: The Variety and Dynamics Of Grey Zones: Attempting A Cross-cmentioning
confidence: 99%
“…recognised. This situation is illustrated by the increasingly precarious situation of trainees in Germany (Giraud and Lechevalier, 2018), or by the unskilled fringe of selfentrepreneurs in Germany and Brazil who return to the informal sector (Rosenfield, 2018). For these groups of workers, institutional change is blocked; the grey zone remains grey and asserts itself as a transitional space for as long as necessary.…”
mentioning
confidence: 99%